Temperaturas de hidrólisis enzimática en variedades de camote para la obtención de alcohol etílico - Miranda Suárez, Pedro Rogelio (2022)
The development of this research focused on evaluating the enzymatic reaction of the enzyme through the maceration temperatures of the must against the three varieties of sweet potato (Ipomoea babatas), for the elaboration of a distilled alcoholic beverage as a result of the development of the transformation of this tuber. An AxB factorial design was used in a completely randomized design, which consisted of 6 treatments and 3 replicates resulting in 18 experimental runs. The study factors were: factor A: three sweetpotato varieties (a1; orange, a2; pedrito and a3; purple guayaco); factor B: maceration time of the must (b1; 62 and b2; 72C). To determine the significant differences between the factors, levels, repetitions and interactions, the Tukey test (p0.05) was performed using a Kruskal-Wallis statistical test, as well as physical-chemical analyses such as pH, °Brix and alcohol content. For the pH results; the purple guayaco variety showed a better result compared to the other varieties under study, because it has the greatest decrease in Total Titratable Acidity (ATT) at the time of enzymatic hydrolysis, giving as the best the T4 treatment (pedrito sweet potato variety + maceration temperature of the must at 72°C), As for the results obtained from the sensory evaluation, the best alcohol according to the characteristics (color, odor, appearance and flavor) was the T4 treatment, indicating that the best treatment is the sweet potato distilled alcoholic beverage.